FITLIGHT Training and Its Influence on Visual-Motor Reactions and Dribbling Speed in Female Basketball Players: Prospective Evaluation Study - Ahmed K Hassan (JMIR Serious Games, 2025)
Abstract BackgroundBasketball exists as a team-based sport played on a court involving intense physical demands because players need continuous movement between offensive and defensive zones. ObjectiveThe aim of the current research was to investigate the impact of a training program implementing FITLIGHT (FITLIGHT Corp) technology on female basketball players’ visual-motor interactions and dribbling speed. MethodsThe study included 28 female basketball players. Participants were divided into 2 groups, experimental group (EG; n=14, mean age 18.29, SD 0.99 y; mean height 174.50, SD 2.10 cm; mean weight 75.36, SD 2.10 kg; mean training 5.64, SD 0.50 y) and control group (CG; n=14, mean age 18.50, SD 0.65 y; mean height 175.64, SD 1.55 cm; mean weight 75.57, SD 1.79 kg; mean training 5.43, SD 0.51 y), in a random manner. Pre- and post-measurements were used, and FITLIGHT training was conducted for 10 weeks with 4 sessions per week. The FITLIGHT training program targeted the elements of visual-motor interactions and dribbling speed for the EG. The CG experienced the same training regimen, but did not participate in the FITLIGHT training. The tests that were adopted and administered were the reaction time in the right hand and left hand, the reactive time (ttttdP ResultsAll the EG improvements were statistically significant (Pdddddddddddd ConclusionsA pairwise comparison between the EG and the CG also revealed a statistically significant difference in the EG, which proved that the EG outperformed the CG. This study provides evidence for the enhanced visual-motor interactions and dribbling speeds of female basketball players who received training that included the use of the FITLIGHT technique.